A Scoping Review of Educational and Training Interventions on Parkinson’s Disease for Staff in Care Home Settings - Stacey Finlay; Tara Anderson; Elizabeth Henderson; Christine Brown Wilson; Patrick Stark; Gillian Carter; Matthew Rodger; Mihalis Doumas; Emma O’Shea; Laura Creighton; Stephanie Craig; Sophie Crooks; et al. (Nursing Reports)
Background/Objectives: Parkinson’s disease (PD) is a complex neurodegenerative disorder that presents significant challenges for care home residents and staff. This scoping review aimed to synthesize evidence on PD education and training available to care home staff, examine existing programs and their effectiveness, and identify gaps in current educational approaches. Methods: A scoping review (ScR) was conducted and guided by the Preferred Reporting Items for Systematic Reviews and Meta-analysis extension for ScR (PRISMA-ScR) checklist. A comprehensive search of six electronic databases was conducted in September 2024. Studies focusing on PD education and training for care home staff were included. Data extraction and quality appraisal were performed, followed by thematic analysis to identify key patterns and themes. Results: Seven studies met the inclusion criteria. The thematic analysis revealed four main themes: improvements in PD knowledge and confidence, improvements in care practices and outcomes, the need for increased specialist education, and the incorporation of communication training. Educational interventions led to significant improvements in staff knowledge, confidence, and care practices. However, these studies also highlighted a critical need for more specialized PD training among care home staff. Conclusions: This review provides evidence of promise regarding the potential impact of PD-specific education on care home staff knowledge and practices. Future research should focus on developing and evaluating comprehensive, tailored educational programs to enhance the quality of care for people with PD in care home settings.